Systems Life Cycle: An Analysis of the Challenges of Implementing an Information System in a Public Health Institution - Lehnhart, Eliete dos Reis; Silva, Tiago Chiapinotto da; Losekann, Vanderléia Leal; Löbler, Mauri Leodir; Tagliapietra, Rafaela Dutra (Revista de Administração da UFSM, 2017)
The objective of this study was to investigate the process of implementation of an information system in a public health institution located in a city in the interior of Rio Grande do Sul. For this we used the case study strategy, through semi-structured interviews with the team responsible for system implementation project, from the concept of life cycle of information systems proposed by Audy, Andrade and Cidral (2005). The results demonstrate that the institution is in the system installation phase. It was also possible to identify some problems faced in the course of the project, as well as direct and indirect gains for public administration and for patients from public municipal health.